Improved Survival in Liver Transplant Recipients Receiving Prolonged‐Release Tacrolimus in the European Liver Transplant Registry. Issue 5 (19th February 2015) - Adam, R.; Karam, V.; Delvart, V.; Trunečka, P.; Samuel, D.; Bechstein, W. O.; Němec, P.; Tisone, G.; Klempnauer, J.; Rossi, M.; Rummo, O. O.; Dokmak, S.; et al.
Abstract : This study was a retrospective analysis of the European Liver Transplant Registry (ELTR) performed to compare long‐term outcomes with prolonged‐release tacrolimus versus tacrolimus BD in liver transplantation (January 2008–December 2012). Clinical efficacy measures included univariate and multivariate analyses of risk factors influencing graft and patient survival at 3 years posttransplant. Efficacy measures were repeated using propensity score‐matching for baseline demographics. Patients with <1 month of follow‐up were excluded from the analyses. In total, 4367 patients (prolonged‐release tacrolimus: n = 528; BD: n = 3839) from 21 European centers were included. Tacrolimus BD treatment was significantly associated with inferior graft (risk ratio: 1.81; p = 0.001) and patient survival (risk ratio: 1.72; p = 0.004) in multivariate analyses. Similar analyses performed on the propensity score‐matched patients confirmed the significant survival advantages observed in the prolonged‐release tacrolimus‐ versus tacrolimus BD‐treated group. This large retrospective analysis from the ELTR identified significant improvements in long‐term graft and patient survival in patients treated with prolonged‐release tacrolimus versus tacrolimus BD in primary liver transplant recipients over 3 years of treatment. However, as with any retrospective registry evaluation, there are a number of limitations that should be considered when interpreting these data. Abstract : The authors perform a retrospective analysis of European Liver Transplant Registry data and identify significant improvements in graft and patient survival in patients treated with prolonged‐ versus immediate‐release tacrolimus over three years of treatment. See editorial by Asrani and O'Leary on page1135 .